Feasibility analysis for the setting up and implementation of a sustainable Waterless Car Wash business (Journal SCIENCEVOLUTION, 2025)
Sustainable development necessitates responsible use of natural resources, particularly water, a critical resource for human survival. This study assessed the feasibility of implementing a waterless car wash system to promote water conservation. A descriptive, exploratory field study was conducted using a 17-item questionnaire administered to 337 vehicle owners in Colonia Panorama, Colonias del Río, San Cayetano, Bosques, and Campestre in Aguascalientes, Mexico. Results showed 83% acceptance of the service at a price of $65.00. Financial analysis yielded a net present value (NPV) of $283,128.71, a minimum acceptable rate of return (MARR/TREMA) of 21.75% (with a 10% risk premium), and an internal rate of return (IRR) of 34.76%, surpassing the MARR. The project demonstrates viability and cost-effectiveness, aligning with sustainable water management goals.
Keywords: Sustainable enterprise; Waterless car wash; Feasibility; Water resources